Coaching for performance, 5th edition the principles and practice of coaching and leadership - Whitmore, John (Gildan Audio, 2019)
Coaching for Performance is the definitive book for coaches, leaders, talent managers, and professionals around the world. An international bestseller, featuring the influential GROW model, this book explains why enabling people to bring the best out of themselves is the key to driving productivity, growth, and engagement. A meaningful coaching culture has the potential to transform the relationship between organizations and employees and to put both on the path to long-term success. Written by Sir John Whitmore, the pioneer of coaching, and Performance Consultants, the global market leaders in performance coaching, this extensively revised and extended edition will revolutionize the traditional approach to organizational culture. Brand-new practical exercises, corporate examples, and coaching dialogues strengthen the learning process, whilst a critical new chapter demonstrates how to measure the benefits of coaching as a return on investment, ensuring this landmark new edition will remain at the forefront of professional coaching and leadership development.
Downloadable audio file. - Title from title screen
Keywords: Business; Affaires; businesses (business enterprises); BUSINESS & ECONOMICS; General; Downloadable audio books; Audiobooks; Livres audio